The ethos of history : time and responsibility - Helgesson, Stefan 1966- HerausgeberIn; Svenungsson, Jayne 1973- HerausgeberIn; Ruin, Hans 1961- VerfasserIn eines Nachworts (Making sense of history, 2018)
"At a time when rapidly evolving technologies, political turmoil, and the tensions inherent in multiculturalism and globalization are reshaping historical consciousness, what is the proper role for historians and their work? By way of an answer, the contributors to this volume offer up an illuminating collective meditation on the idea of ethos and its relevance for historical practice. These intellectually adventurous essays demonstrate how ethos--a term evoking a society's "fundamental character" as well as an ethical appeal to knowledge and commitment--can serve as a conceptual lodestar for history today, not only as a narrative, but as a form of consciousness and an ethical-political orientation"--